KUKTEM interactive map - Mohd Rofizal, Mustapa (2005)
Nowadays, many map developer are moving toward an electronics era by converting the static map to the electronic interactive map.It is because an electronics map offer more beneficial features such as data retrieval, attractive, great for fast orientation and the important things is the map must be easy to use and helpful. Besides, by implementing in the web base platform, it also can be use as a marketing tool for outsider's attraction for a promotion. However,this system had not been implementing yet in KUKTEM. So, the idea to transform the available static map into an interactive map had leaded in the process to develop this system.The system should have a usable interface by implementing location based query.The system will involve data visualization in order to perform the map in an interactive way.The expected result from this system is it will help KUKTEM community and outsiders to know more about KUKTEM which user can see KUKTEM in the interactive map.